IBM Peran Kader Dalam Lansia Dengan Demensia di Desa Deliksari, Gunungpati - Novita Wulan Sari; Margiyati Margiyati (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
This research aims to analyze the role of cadres in caring for elderly people with dementia in Deliksari Village, Gunungpati. Cadres are individuals who are specially trained to provide health and social support in their communities. In this context, they have a responsibility to help families and elderly people experiencing dementia through various programs and activities focused on improving quality of life and preventing further cognitive decline. This study uses a qualitative approach with observation methods, in-depth interviews and document analysis to obtain relevant data. The research results show that cadres play an important role in providing health information, care training, and emotional support to families and the elderly. They also act as a link between the community and formal health services, assisting in the early detection and more effective management of dementia